The war of the worlds - Wells, H.G. 1866-1946 Herbert George Wells; Wells, H. G. (Herbert George), 1866-1946. (Hong Kong : Oxford University Press, 1975)
The War of the Worlds is a science fiction novel by English author H. G. Wells. It was written between 1895 and 1897,[2] and serialised in Pearson's Magazine in the UK and Cosmopolitan magazine in the US in 1897. The full novel was first published in hardcover in 1898 by William Heinemann. The War of the Worlds is one of the earliest stories to detail a conflict between humankind and an extraterrestrial race.[3] The novel is the first-person narrative of an unnamed protagonist in Surrey and his younger brother in London as southern England is invaded by Martians. It is one of the most commented-on works in the science fiction canon
Keywords: Graphic novels; Science fiction; Graphic novels